What predicts children's active transport and independent mobility in disadvantaged neighborhoods?. (March 2017) - Veitch, J.; Carver, A.; Salmon, J.; Abbott, G.; Ball, K.; Crawford, D.; Cleland, V.; Timperio, A.
Abstract: This study examined two year changes in children's active transport and independent mobility and prospective associations between individual, social and physical environmental predictors of interest and these behaviors two years later. Overall, 43.5% of children (12.0±2.1 years) used active transport on the school journey at T1 and at T2 (p=0.77), and 35.3% engaged in independent mobility on the school journey at T1 and 29.6% at T2 (p=0.07). Enjoyment, parental safety concerns, and proximity to walking tracks were associated with independent mobility on the school journey. Road safety and social norms were associated with active transport and independent mobility to local destinations. These factors provide potential targets for interventions. Highlights: 43% of children habitually used active transport on the school journey. 35% engaged in independent mobility (IM) on the school journey. Enjoyment, safety and walking tracks were associated with IM on school journey. Road safety was negatively associated with active transport to local destinations. Social norms were associated with independent mobility to local destinations.